2017
DOI: 10.1038/srep40710
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of a P1-like bacteriophage carrying CTX-M-27 in Salmonella spp. resistant to third generation cephalosporins isolated from pork in China

Abstract: The aim of this study was to elucidate the epidemiology of third generation cephalosporin resistant Samonella isolates from pork of a slaughterhouse in China and the features of transferable elements carrying blaCTX-M genes. One hundred and twenty-six (7.3%) Salmonella isolates were identified; S. Derby and S. Rissen were the most two prevalent serotypes. Among these isolates 20 (15.8%) were resistant to third generation cephalosporins and nine of them carried blaCTX-M-27. S1-PFGE and replicon typing of blaCTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 43 publications
5
58
0
Order By: Relevance
“…Despite extensive investigations, the transmission mechanisms during natural conditions remains unknown. Several attempts on mobilizing wild-type bacteriophages have failed (38). However, in this study we detected a high frequency of concurrent IncI1 plasmid and P1 phage transmission during liquid conjugation, suggesting that of co-transfer mechanisms.…”
Section: Discussionmentioning
confidence: 45%
“…Despite extensive investigations, the transmission mechanisms during natural conditions remains unknown. Several attempts on mobilizing wild-type bacteriophages have failed (38). However, in this study we detected a high frequency of concurrent IncI1 plasmid and P1 phage transmission during liquid conjugation, suggesting that of co-transfer mechanisms.…”
Section: Discussionmentioning
confidence: 45%
“…A total of nine predicted phage elements were found across the five A. sobria isolates (Supplementary Table 3 ). Seven of those prophages were found in JF2635, of which only two were presumably intact: a Phi018p-like element ( Beilstein and Dreiseikelmann, 2008 ) and a SJ46-like element ( Yang L. et al, 2017 ). Only one intact prophage, a Fels-2-like element is found in both CECT 4245 and 08005 strains (clade 1), whilst only one prophage, a 9.5 kb Phi018p-like element (presumably incomplete) was found in both TM12 and TM18 strains (clade 2).…”
Section: Resultsmentioning
confidence: 99%
“…Albany strain isolated from chicken meat in Vietnam was found to be resistant against ceftriaxone (3rd generation cephalosporin) but not cefepime (4th generation cephalosporin) ( Ta et al, 2014 ). A recent study on NTS isolates from pork in China has shown a relatively high prevalence of resistance (15.8%) against 3rd generation cephalosporins (ceftiofur, cefotaxime, ceftriaxone and ceftazidime) ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%